Structural insights of the conserved "priming loop" of hepatitis B virus pre-genomic RNA. Issue 20 (29th November 2022) - LeBlanc, Regan M.; Kasprzak, Wojciech K.; Longhini, Andrew P.; Olenginski, Lukasz T.; Abulwerdi, Fardokht; Ginocchio, Stefano; Shields, Brigit; Nyman, Julie; Svirydava, Maryia; Del Vecchio, Claudia; Ivanic, Joseph; Schneekloth, John S.; et al.
Abstract: Initiation of protein-primed (-) strand DNA synthesis in hepatitis B virus (HBV) requires interaction of the viral polymerase with a cis -acting regulatory signal, designated epsilon (ε), located at the 5′-end of its pre-genomic RNA (pgRNA). Binding of polymerase to ε is also necessary for pgRNA encapsidation. While the mechanistic basis of this interaction remains elusive, mutagenesis studies suggest its internal 6-nt "priming loop" provides an important structural contribution. ε might therefore be considered a promising target for small molecule interventions to complement current nucleoside-analog based anti-HBV therapies. An ideal prerequisite to any RNA-directed small molecule strategy would be a detailed structural description of this important element. Herein, we present a solution NMR structure for HBV ε which, in combination with molecular dynamics and docking simulations, reports on a flexible ligand "pocket", reminiscent of those observed in proteins. We also demonstrate the binding of the selective estrogen receptor modulators (SERMs) Raloxifene, Bazedoxifene, and a de novo derivative to the priming loop. Communicated by Ramaswamy H. Sarma